PERAN MANAJEMEN DAKWAH DALAM PENGELOLAAN SUMBER DAYA MANUSIA DI PENDIDIKAN ISLAM - Danu Atmaja, Kemas Haykal (Mushawwir Jurnal Manajemen Dakwah dan Filantropi Islam, 2023)
People are one of the most important resources in management means. The importance of this human resource is recognized by all management levels and managers education. Even today, with the advent of advanced technology, the human factor continues to play an integral role in the club's success. Human resources are an essential part of an organization Since humans are the first and main element of previous management other aspects. Human resource management therefore plays a central role Manage and achieve organizational goals educational institution. Human resources must be properly regulated Through its capabilities, enable these people to play a role in the task functions of relevant agencies. Keyword: Management, human resources, educational institutions